2010
DOI: 10.1590/s1516-80342010000100016
|View full text |Cite
|
Sign up to set email alerts
|

Estudo do papel do contexto linguístico no tratamento do desvio fonológico

Abstract: RESUMOObjetivo: Verificar a aplicabilidade dos ambientes favoráveis e neutros, obtidos a partir de dados de fala de crianças sem alteração de linguagem, no tratamento do desvio fonológico. Métodos: Seis crianças, com idade média de seis anos, com desvio fonológico, foram tratadas através do modelo ABAB -Retirada e Provas Múltiplas. As palavras selecionadas para o tratamento continham os ambientes favoráveis e neutros para a aquisição do /r/ segundo estudos de base teórica gerativa e gestual. A evolução terapêu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 11 publications
1
15
1
2
Order By: Relevance
“…It was verified in a CG subject that there was phonological system regression. This finding is described in literature (23,24) , which mentions that if the phonological acquisition is a non linear process, it is clearly observed that there are moments of decrease in the ascending line of the typical development, with short periods of regression in the segment acquisition.…”
Section: Discussionsupporting
confidence: 66%
“…It was verified in a CG subject that there was phonological system regression. This finding is described in literature (23,24) , which mentions that if the phonological acquisition is a non linear process, it is clearly observed that there are moments of decrease in the ascending line of the typical development, with short periods of regression in the segment acquisition.…”
Section: Discussionsupporting
confidence: 66%
“…The phoneme is the smallest linguistic unit, simpler and more unique representative sound of the languages. Phonology is a component of the language that manages the repertoire of phonemes and organizes the way they are produced 2,3 . Throughout their development, the children learn to ignore some phonemes and keep attention to those that are most used in their mother tongue 4 .…”
Section: Conflict Of Interest: Non-existentmentioning
confidence: 99%
“…This hypothesis is supported by studies of phonological change following treatment involving target words which provide a favorable environment for target sounds 3,4,7,11,12,14,21,22 .…”
Section: Introductionmentioning
confidence: 84%
“…However, a comparative study 14 of favorable and neutral environments, classified based on data drawn from typically-developing children, found that target words providing a neutral context (/r/ in a stressed syllable, preceded by /o/ and followed by / /) produced larger changes in the phonological system of six children treated for phonological disorders than favorable target words (target sound preceded by the vowel /i/ and followed by /u/; target sound preceded by /a/ and followed by /e/). These findings suggest that favorable contexts determined based on data from typically-developing children may not apply to children with phonological disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation